Inclusive Driver's License Service Model Based on the Needs of Local Communities - Akbar Rizky Pratama Mohamad; Sri Yulianty Mozin; Rahmatia Pakaya (Public Policy Journal, 2026)
The research analyzed the implementation of Driver's License services at the Gorontalo City Police. The research uses a qualitative approach of case studies through in-depth interviews, observations, and document analysis, data is analyzed thematically based on the dimensions of individual, group, and social well-being (Anderson et al. 2013). The results of the study showed that there was a gap between Standard Operating Procedures and field practices, characterized by inconsistencies in service times, irregular queues, fraudulent practices, lack of assistance for vulnerable groups, and limited disability-friendly facilities. This condition has an impact on increasing individual stress and dissatisfaction, inequality of access between groups, and declining public trust in service institutions. Based on these findings, this study formulated an Ideal Model of Well-Being & Public Value-Based Driver's License Services (Fathya et al., 2025), which integrates: (1) procedural transparency and accountability; (2) equality and inclusivity of access, including for persons with disabilities and vulnerable groups; (3) responsiveness and empathy of officers; (4) a fair queue system and free of trade intervention; and (5) collaboration with social organizations as mediators of community needs. This model emphasizes that the quality of services is not only measured by operational efficiency, but also by its ability to generate public value in the form of access justice, citizen satisfaction, and strengthening trust between the state and society. This research contributes to expanding the application of transformative approaches in the context of public services at the local level